Between Nationalism and the Flat World of Thomas Friedman - Cristian Spiridon (CES Working Papers, 2013)
The present paper aims to disseminate the impact of globalization on the nation-state throughout the history. The research objective consists in the reviewing of the assertion of the globalization phenomenon and the conflicts it stirred at the national level by reasons related to cultural, economic, social or political issues. The analysis will be conducted by two antagonistic positions: an optimistic view according to which globalization has a positive effect overall and a pessimistic one under which globalization causes the decline of the nation-state. The main findings will show that nationalism is not doomed to disappear, but instead it will adapt over time and will steal from the benefits globalization brings everything that culturally, politically, socially, or economically suits to a certain nation.
Keywords: A10; B11; B20; F10; F60; 330; globalization; nationalism; nation-state; liberal democracy; Western World Romania